2006
DOI: 10.1200/jco.2006.07.4799
|View full text |Cite
|
Sign up to set email alerts
|

Early Invasive Cervical Cancer: Tumor Delineation by Magnetic Resonance Imaging, Computed Tomography, and Clinical Examination, Verified by Pathologic Results, in the ACRIN 6651/GOG 183 Intergroup Study

Abstract: In patients with cervical cancer, MRI is superior to CT and clinical examination for evaluating uterine body involvement and measuring tumor size, but no method was accurate for evaluating cervical stroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
152
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(161 citation statements)
references
References 56 publications
4
152
0
5
Order By: Relevance
“…In studies by Hricak et al and Mitchell et al, in locally advanced cervical cancers, imaging modalities were superior for staging purposes (Hricak et al, 2005;Mitchell et al, 2006;Shirazi et al, 2014). In contrast, clinical staging was found to be more effective in a study by Hancke et al (Hancke et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…In studies by Hricak et al and Mitchell et al, in locally advanced cervical cancers, imaging modalities were superior for staging purposes (Hricak et al, 2005;Mitchell et al, 2006;Shirazi et al, 2014). In contrast, clinical staging was found to be more effective in a study by Hancke et al (Hancke et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…As the American College of Radiology Imaging Network (ACRIN )6651/GOG 183 Intergroup study showed [5], current MRI technology delineates tumour boundaries accurately and is frequently used to guide both treatment development and application [3,4]. In particular, MRI …”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that MRI may predict the extent of disease more accurately than clinical staging [5]. With regard to bladder invasion, studies specifically tested the diagnostic accuracy of MRI against cystoscopic examination and/or surgical sampling as reference standards [6][7][8][9][10].…”
mentioning
confidence: 99%
“…In the staging evaluation of cervical cancer, CT and MR imaging are generally equivalent for the assessment of lymph node and metastatic involvement, but MR imaging is superior in delineating tumor extent within the uterus and direct extensions of tumor to adjacent pelvic tissues (19,20), including bladder invasion, parametrial extension, and rectal and perirectal involvement. Ancillary findings that may or may not be related to the tumor but can influence the treatment approach, such as distortion or retroversion of the uterus, uterine fibroids, ovarian findings, and other pelvic abnormalities, can be readily evaluated with MR imaging.…”
Section: Mr Imagingmentioning
confidence: 99%